The Implementation of Presentation Practice Production (PPP) Technique to Improve Students’ Speaking Skill by Using Picture Card as a Media - Artha, Dewi Juni (Jurnal Riset Ilmu Pendidikan, 2022)
The objective of this research was to find out the process of implementation of Presentation Practice Production to improve students’ speaking skill. The study was conducted by using two cycles, where each cycle consists of three meetings and each meeting include four steps, namely: Planning, Implementing, Observing, and Reflecting. The qualitative datas were taken from the result of the test that had been given to the students. The test that was given still relevant to the topic that was taught and discussed in the classroom in every cycle. There were two cycles that were considered of four meetings in this research and the test was given in the last of each cycle. The Quantitative data was taken test that gave to the students in the last of each cycle. The result indicated that there was an increasing on the students speaking skill by using presentation, practice, and production (PPP) technique. The mean of the first cycle were 66 it was good enough. The mean of second cycle were 79 it indicated that the scores and the mean in second cycle were better than the first cycle. The percentage of students who got point ? 70 also grew up. In the pre-test, the students who got point ? 70 up were only 2 students (10%). In the post- test of cycle (I) students who got point ? 70 up were 11 students (55%) it means that there were an increasing about 45%. The post-test of cycle (II), students who got point 70 to up there were 20 students (100%) and the increasing were about 45%. For the total increasing of the students’ score from pre-test to post-test of cycle two (II) were100%. In other words, the students’speaking skill improved and became well in the first meeting to the next meeting